Caracterização de perfilhos do capim-paiaguás diferido sob diferentes alturas e períodos - Oliveira, Ayrton Elvis Silva (2022)
Pasture deferment is a strategy that can mitigate the effects of seasonal forage production. The aim of this study is to evaluate changes in tiller structure of Paiaguás grass, when deferred at different heights and periods. The deferments used in July, August and September until November (corresponding to periods of 120, 90 and 60 days, respectively) and two heights (15 and 30 cm) were evaluated in split plots, with three replications, totaling 18 experimental units (12.5 m² each). When compared to the one deferred in July, Paiaguás grass deferred in September showed smaller stems (46.7 versus 115.6 cm), shorter length (11.13 cm versus 23.44 cm), less dead leaves (2.0 versus 6.0), a lower percentage of dead forage (15.34 versus 29.83), higher population density of up to 40 cm tiller (50 versus 18) and a higher percentage of live leaf blade at 15 cm (42 .77 versus 20.45) and 30 cm (35.90 versus 21.38), when compared to the months of August and July. The deferment in July resulted in lower percentages of up to 40 cm and aerial tillers (49 versus 100 tillers/m²), in relation to the deferment in September. The Paiaguás grass deferment in September at 15 cm resulted in a higher percentage of live leaf blade (42.7 versus 35.9%) in relation to the height of 30 cm in the same month. The tiller deferred in September has the best structural characteristics compared to tillers deferred in the other months. 75% of the variables analyzed were not influenced by the different heights of the pasture at the beginning of deferment. Thus, the deferment in September at 15 cm can be recommended if a more youthful tiller profile is desired.